2014
DOI: 10.1002/2013pa002501
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of shoaling of the Central American Seaway determined from modeling Nd isotopes

Abstract: The Central American Seaway played a pivotal role in shaping global climate throughout the late Cenozoic. Recent geological surveys have provided new constraints on timing of the seaway shoaling, while neodymium isotopic (ε Nd ) data measured on fossil teeth, debris, and ferromanganese crusts have helped define the history of water masses in the region. Here we provide the first 3-D simulations of ε Nd responses to the shoaling seaway. Our model suggests that a narrow and shallow seaway is sufficient to affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
105
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(120 citation statements)
references
References 71 publications
15
105
0
Order By: Relevance
“…This episode of species dispersal between the previously disconnected landmasses of South America and Central-North America was the product of the complex rise of the isthmus of Panama, which started ca. 10-12 Ma Montes et al 2012;Sepulchre et al 2014) and culminated with the full rise of the isthmus ca. 3.5 Ma (Coates et al 2003(Coates et al , 2004.…”
Section: Great American Biotic Interchange (Gabi)mentioning
confidence: 99%
“…This episode of species dispersal between the previously disconnected landmasses of South America and Central-North America was the product of the complex rise of the isthmus of Panama, which started ca. 10-12 Ma Montes et al 2012;Sepulchre et al 2014) and culminated with the full rise of the isthmus ca. 3.5 Ma (Coates et al 2003(Coates et al , 2004.…”
Section: Great American Biotic Interchange (Gabi)mentioning
confidence: 99%
“…Fossil evidence demonstrated that the procyonids predate this episode and are among the first North American immigrants recorded in South America (Marshall et al 1979;Linares 1981;Baskin 1982;Berman 1994;Soibelzon andPrevosti 2007, 2012;Woodburne 2010;Prevosti and Soibelzon 2012). A full closure of the Central American Seaway (or CAS, the oceanic pathway along the tectonic boundary between South America and the Panama Block) occurred by 12-10 Ma, ending the exchange of deep and intermediate waters between the Caribbean and the Pacific (Coates et al 2004;Montes et al 2012a, b;Sepulchre et al 2014). Intermittent exchange of shallow waters between the Pacific and the Caribbean continued in the 10-to 3.5-Ma interval, along places other than the CAS, greatly enhancing the dispersal of biota across the isthmus , previous to its full closure that occurred at about 4.2-3.5 Ma (Haug et al 2004).…”
Section: Procyonids and The Great American Biotic Interchangementioning
confidence: 99%
“…(For interpretation of the references to colour in this figure legend, the reader is referred to the web version of this article.) on changes in benthic foraminifera assemblages (Duque-Caro, 1990) and neodynium isotopic data both measured on fish teeth and foraminifera, and simulated (Newkirk and Martin, 2009;Osborne et al, 2014;Sepulchre et al, 2014). In a recent study, Montes et al (2012) used U-Pb-Th dating on zircons from granitoid samples, geochemical analyses of basaltic samples, and paleomagnetic samples from cores drilled in Panama to argue that the Panamanian Gateway might have closed as early as 15 Ma.…”
Section: Introductionmentioning
confidence: 99%